Deconstructing Local Adaptation Plans for Action (LAPAs) - Analysis of Nepal and Pakistan LAPA initiatives - Chaudhury, Abrar S.; Sova, Chase; Rasheed, T; Thornton, Thomas F.; Baral, P.; Zeb, A (2014)
This paper analyses the organizational and implementation design strategies of two ongoing Local Adaptation Plan for Action (LAPA) initiatives in Nepal and Pakistan. LAPA is considered an answer for institutionalized local-level adaptation planning that aims to capture local needs and direct resources to where, when and by whom these are most needed. While both Nepal and Pakistan LAPAs have similar objectives of bottom-up planning, the operational and structural designs of the two LAPAs are very distinct, leading to different outcomes. Different internal and external factors such as age and size of LAPA, technology, local institutional arrangements, core process and environment also exert significant structural tensions on the planned organizational design of LAPAs that may inhibit delivery of their objectives.